If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -3 = m Reorder the terms: -3 + 2n = m Solving -3 + 2n = m Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2n = 3 + m Combine like terms: -3 + 3 = 0 0 + 2n = 3 + m 2n = 3 + m Divide each side by '2'. n = 1.5 + 0.5m Simplifying n = 1.5 + 0.5m
| 4*13/8 | | 5x-8x+x= | | -3/2(y-8)-1/4y= | | 9z-11=61 | | 2s-21=-22+s | | 5(7+8x)+11= | | 15+x=3x-15 | | -5(a-1)=-35 | | 2x^4+22x^2-15x+7=0 | | 4=32/? | | 17=2-4K | | 9x-22=-8+2x | | 3x-8+4+5x-2x=x-3+2x-1-9 | | -8=w+5w-10w-20 | | 4x+6=2x+15 | | 20x+5y-20=21x+4 | | -2(6a-7)=31-5a | | 4a+b=22 | | 3x^3y^3/x^2y | | 3x/5=2x/3=1 | | f(x)=(x^2-4x+6)-4 | | -7f+3-4=30 | | 3n-5=-8-10n-6(6+5n)-4 | | 2x6x6x6/(4x-4) | | 9n-13=5 | | -32=72 | | 5.37/0.001 | | -13=-16+9k | | 195=(x*16) | | 4(x+7)(x+7)=11 | | 93=4x+7(3x-5)+3 | | 37/8-15/8 |